2016
DOI: 10.1186/s40064-016-2115-7
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and prevalence of Vibrio parahaemolyticus in seafood: a systematic review and meta-analysis

Abstract: Vibrio parahaemolyticus is an important seafood borne human pathogen worldwide due to it occurrence, prevalence and ability to cause gastrointestinal infections. This current study aim at investigating the incidence and prevalence of V. parahaemolyticus in seafood using systematic review-meta-analysis by exploring heterogeneity among primary studies. A comprehensive systematic review and meta-analysis of peer reviewed primary studies reported between 2003 and 2015 for the occurrence and prevalence of V. paraha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 76 publications
1
46
0
Order By: Relevance
“…Moreover, as the most frequently studied seafood candidate for the prevalence of vibrios, oysters have been reported to harbor multidrug‐resistant Vibrio spp. (Odeyemi, ). Kang, Shin, Jang, Jung, and So () reported oyster‐borne V. alginolyticus in Korea showing 100% resistance to ampicillin and vancomycin, and 26.7% resistance to cephalothin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, as the most frequently studied seafood candidate for the prevalence of vibrios, oysters have been reported to harbor multidrug‐resistant Vibrio spp. (Odeyemi, ). Kang, Shin, Jang, Jung, and So () reported oyster‐borne V. alginolyticus in Korea showing 100% resistance to ampicillin and vancomycin, and 26.7% resistance to cephalothin.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, as the most frequently studied seafood candidate for the prevalence of vibrios, oysters have been reported to harbor multidrug-resistant Vibrio spp. (Odeyemi, 2016). Kang, Shin, Jang, Jung, and So (2016) which was parallel to this study.…”
Section: Virulence-related Gene Profilesmentioning
confidence: 91%
“…This pathogen is typically isolated in warm seawater and is rarely isolated when the temperature of seawater is under 13 to 15 °C (Kaneko & Colwell, 1975). Significant investigation and analysis of the presence of V. parahaemolyticus in seafood were presented by Odeyemi (2016) recently in a systematic review and meta‐analysis of 48 studies published between 2003 and 2015. The author revealed that the concentration of V. parahaemolyticus was higher in oysters than in other seafood products; the presence of V. parahaemolyticus in oysters, clams, fish, shrimp, and mussels was 63.4%, 52.9%, 51.0%, 48.3%, and 28.0%, respectively (Odeyemi, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Significant investigation and analysis of the presence of V. parahaemolyticus in seafood were presented by Odeyemi (2016) recently in a systematic review and meta‐analysis of 48 studies published between 2003 and 2015. The author revealed that the concentration of V. parahaemolyticus was higher in oysters than in other seafood products; the presence of V. parahaemolyticus in oysters, clams, fish, shrimp, and mussels was 63.4%, 52.9%, 51.0%, 48.3%, and 28.0%, respectively (Odeyemi, 2016). A high concentration of V. parahaemolyticus is expected because oysters are aquatic filter feeders; consequently, they accumulate high concentrations of the bacterial pathogen V. parahaemolyticus .…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] The rst reported outbreak of seafood borne disease due to V. parahaemolyticus was in Japan in 1950 in which 20 people were reported dead while over 270 people were likewise hospitalized. 7 There also be outbreak in China, Spain, Chile, Peru and other coastal state. A survey about the incidence rate of V. parahaemolyticus from 1998-2013 in China, the positive rate of intestinal pathogenic bacteria of V. parahaemolyticus is up to 83%.…”
Section: Introductionmentioning
confidence: 99%